Comparison of the early period effects of bone marrow-derived mesenchymal stem cells and platelet-rich plasma on the Achilles tendon ruptures in rats - Yuksel, Serdar; Gulec, M. Akif; Gultekin, M. Zeki; Adanir, Oktay; Caglar, Aysel; Beytemur, Ozan; Kucukyildirim, B. Onur; Avci, Ali; Subasi, Cansu; Inci, Cigdem; Karaoz, Erdal (TAYLOR & FRANCIS INC, 2016)
Introduction: This study aims to histopathologically, biomechanically, and immunohistochemically compare the fourth-week efficiencies of local platelet-rich plasma (PRP) and bone marrow-derived mesenchymal stem cell (rBM-MSC) treatments of the Achilles tendon ruptures created surgically in rats. Materials and Methods: The study included 35 12-month-old male Sprague Dawley rats, with an average weight of 400-500 g. Five rats were used as donors for MSC and PRP, and 30 rats were separated into MSC, PRP, and control groups (n = 10). The Achilles tendons of the rats were cut transversely, the MSC from bone marrow was administered to the MSC group, the PRP group received PRP, and the control group received physiological saline to create the same surgical effect. In previous studies, it was shown that this physiological saline does not have any effect on tendon recovery. Thirty days after the treatment, the rats were sacrificed and their Achilles tendons were examined histopathologically, immunohistochemically, and biomechanically. Results: The use of rBM-MSC and PRP in the Achilles tendon ruptures when the tendon is in its weakest phase positively affected the recovery of the tendon in histopathologic, immunohistochemical, and biomechanical manners compared to the control group (p < 0.05). While the levels of pro-inflammatory cytokines TNF-, IFN, and IL 1 were significantly low, the levels of anti-inflammatory cytokines and growth factors playing key roles in tendon recovery, such as IL2, VEGF, transforming growth factor-beta, and HGF, were significantly higher in the MSC group than those of the PRP and control groups (p < 0.05). In the MSC group, the Delta IFmax (mm) value was significantly higher (p ? 0.05) than that in the PRP and control groups. Conclusion: rBM-MSC and PRP promote the recovery of the tendon and increase its structural strength. The use of PRP and MSC provides hope for the treatment of the Achilles tendon ruptures that limit human beings' functionalities and quality of life, particularly for athletes. It is thought that the use of MSC can be more effective for tendon healing; hence, more extensive and advanced studies are needed on this topic.
Keywords: Achilles tendon rupture; bone marrow cells; mesenchymal stem cells; platelet-rich plasma; rats; ENDOTHELIAL GROWTH-FACTOR; REPAIR; ANGIOGENESIS; THERAPY; STIMULATION; INJECTION; INJURIES; IMPROVE; MODEL; PRP; Cell Biology; Orthopedics